A Cantor-Bernstein type theorem for effect algebras by Jenca G.

By Jenca G.

We turn out that if E1 and E2 are a-complete impression algebras such that E1 is an element of E2 and E2 is an element of E1, then E1 and E2 are isomorphic.

Show description

Read Online or Download A Cantor-Bernstein type theorem for effect algebras PDF

Best algebra books

A Treatise on Universal Algebra with Applications

Symbolic Reasoning allied to bland A lgebra. the manager examples of such platforms are Hamilton sQ uaternions, Grassmann sC alculus of Extension and Boole sS ymbolic good judgment. Such algebras have an intrinsic worth for separate certain learn; they are also priceless of a comparative learn, for the sake of the sunshine thereby thrown at the basic thought of symbolic reasoning, and on algebraic symbolism particularly.

Extra info for A Cantor-Bernstein type theorem for effect algebras

Sample text

RIGHT-EXACTNESS 39 sequence to obtain the top-most exact row in the following diagram I ⊗R M f 0  / IM / R ⊗R M g  /M / (R/I) ⊗R M /0 h  / M/IM / 0. The vertical maps are given by f (i⊗m) = im and g(r⊗m) = rm and h(r⊗m) = rm. Show that these maps are well-defined and make the diagram commute. The map f is an epimorphism, and g is an isomorphism. 15. Let ϕ : R → S be a homomorphism of commutative rings. Let M be an R-module, and let N be an S-module. (a) Prove that if S is flat over R and N is flat over S, then N is flat over R.

The other parts of bilinearity are verified similarly. Since h is R-bilinear, the universal property for tensor products yields a welldefined R-module homomorphism H : M ⊗R N → (M ⊗R N )/K satisfying the following: for m ⊗ n ∈ M ⊗R N , fix m ∈ M and n ∈ N such that f (m) = m and g(n) = n ; then H(m ⊗ n ) = m ⊗ n). It follows readily that the composition Hφ : (M ⊗R N )/K → (M ⊗R N )/K is the identity on (M ⊗R N )/K, so φ is injective as desired. 2. The maps µZ2 : Z → Z and ✶Z/2Z : Z/2Z → Z/2Z are both injective.

4. Let R be a commutative ring, and let M and N be R-modules. Let I, J ⊆ R be ideals such that IM = 0 and JN = 0. Then (I + J)(M ⊗R N ) = 0. To show this, it suffices to show that I(M ⊗R N ) = 0 and J(M ⊗R N ) = 0. Let a ∈ I, and let µM a : M → M denote the homothety m → am. Our assumption implies that M µM a = 0 = µ0 . 3 implies that the induced map M ⊗R N → M ⊗R N is given by multiplication by a, and by multiplication by 0. That is, multiplication by a on M ⊗R N is 0. This implies that a(M ⊗R N ) = 0, and hence I(M ⊗R N ) = 0.

Download PDF sample

Rated 4.58 of 5 – based on 28 votes